Self-regulation across time of first-generation online learners - Lucy Barnard-Brak; Valerie Osland Paton; William Y. Lan (Association for Learning Technology, 2010)
Self-regulatory skills have been associated with positive outcomes for learners. In the current study, we examined the self-regulatory skills of students who are firstgeneration online learners over the course of their first semester of online instruction. The purpose of this study is to determine whether the online selfregulatory skills of learners changed across time as associated with being immersed in their first online learning environment. The results of the current study indicate no significant differences in the online self-regulatory skills of learners across time. Results suggest that environmental factors such as being immersed in an online learning environment for the first time is not, in and of itself, associated with the development of self-regulatory skills of online learners. We conclude that the design of online courses needs to consider ways of developing self-regulatory skills as these skills are not automatically developed with students' online learning experiences.